SELEKSI MIKROBA RIZOSFER ANTAGONIS TERHADAP BAKTERI Ralstolnia solanacearum PENYEBAB PENYAKIT LAYU BAKTERI PADA TANAMAN JAHE DI LAHAN TERTINDAS - Hendri Bustamam (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2006)
Bacterial wilt disease caused by Ralstolnia solanacearum had decreased the ginger production. Saphrophyte and antagonistic microbe are potential to control this disease by Integrated application. This microbes could be found at supressive land for pathogens. Research due to select the potential microbes to control bacterial wilt disease on ginger. Microbe was isolated from rhizosfer soil and root of healthy crop on infected ginger cropping by Ralstolnia solanacearum in Bengkulu by plate dilution methode using Pepton Glucose Agar (PGA) and Ginger-Potato Dextrose Agar (GPDA). Antagonistic was tested by Double Culture Technique on PGA and GPDA. Selected saphrophyte and antagonistic isolat was cultured on organic medium and tested to ginger crop that grown on infected soil. Disease development was observated until 5 months-age crop. The result of this experiment had isolated 4 fungi isolates and 4 bacteria isolates that potential as biocontrol agent to Ralstolnia solanacearum. Tested on Var. Badak ginger cropping indicated that all isolates had reduced 64-84% of diseases. Five Isolates of Pennicilium digitatum, Trichoderma harzianum, T. viride, Achromobacter sp., and Pseudomonas fluorescence was protected the crop to zero diseases; while three isolates of Trichoderma koningii, Bacillus sp., and Pseudomonas putida was protected the crop to 4% infected. Amundment of 12 isolates cultured on organic matter can improve the growth of false stem 11.11 – 96.97%; leave number 8.29 - 156%; and plant height 27.68 – 93.75%.